Effect of extra-large compound calcium-aluminosilicate inclusions on cracking of camshafts. (March 2020) - Xu, Xiao-lei; Yu, Zhi-wei; Mao, Sheng-mei
Highlights: Camshafts cracked after finishing final heat treatment induction-quenching. Thermal stress and transformation stress developed on matrix surrounding inclusion. Numerous extra-large calcium-aluminosilicate inclusions were found in crack origins. The presence of extra-large inclusions was responsible for cracking of camshaft. Abstract: About one-hundred out of three-hundred camshafts were found to crack in varying degrees after finishing final heat treatment of induction-quenching. The cracked camshafts were made from one steel ingot of same furnace number. The failed camshafts are used in truck diesel engine with six cylinders. Stereomicroscope observation showed that several longitudinal and radial cracks were presented on the external surfaces of journals and cams and the side of journals of camshafts. Numerous extra-large elongated compound inclusions of calcium-aluminosilicate (CaO⋅Al2 O3 ⋅SiO2 ) along the longitudinal of camshaft were found on the fracture surfaces. Fracture surfaces characteristically "woody" in appearance or lamellar and deep groove fracture topography were confirmed to be associated with inclusion distribution along the longitudinal direction of camshaft. Metallographic examination indicated that the camshaft material had a very low purity, especially in the surface region of camshafts, i.e. crack origin regions. The total index of oxide inclusion of the metallographic samples from the smoothed fracture surfaces was evaluated to be K4 = 181 according to DIN standard, much higher than the specified index, K4 ≤ 30. During induction-quenching process, a hoop tensile thermal stress and a hoop tensile transformation stress would develop on the matrix surrounding the compound inclusion of calcium-aluminosilicate due to the significant difference in the thermal expansion coefficients between them and the volume expansion of matrix in the surface region resulting from the transformation of austenite to martensite. When the superimposed stress of both stresses was greater than the tensile strength of matrix material in the surface region, the micro-cracks along the radial of compound inclusion would develop on the matrix surrounding the compound inclusion to lead to cracking of camshaft.